The Literary Avatars of Christian Sacramentality, Theology and Practical Life in Recent Modernity - Zirra, Ioana; Zirra, Ioana; Potter, Madeleine (Peter Lang, 2015)
Twelve Anglicists (from France, America, Poland, and Romania) who met in Bucharest to debate Religion and Spirituality in Literature and the Arts at the ACED Conference in June 2015 join their voices in demonstrating the vitally spiritual power of Christianity in the recently modern world (in twentieth and twenty-first century literature and society). Poetry (by Eliot, Yeats, Heaney, David Jones, Hill, G.M. Brown) and fiction (Henry James, Lodge, Evelyn Waugh, Flannery O$1 (BConnor, Rose Macaulay and Ron Hansen), interpreted with (Thomist and more recent) theology (J.H. Newman$1 (Bs, Paul Tillich$1 (Bs, Hans Urs von Balthasar$1 (Bs, De Certeau$1 (Bs) and philosophy (from Plato to Gadamer) in mind, give heartening suggestions for transcending, along Catholic, Anglican, and Orthodox lines, the modern secular ethos.s